Analisis Pengelolaan Alokasi Dana Desa (ADD) di Desa Abbatireng Kecamatan Gilireng, Kabupaten Wajo - Andi Siti Sri Hutami (Departemen Ilmu Pemerintahan Fisip Unhas, 2017)
The result of the research showed: First, process management of ADD, include planning, implementation, structuring, reporting, and accountability. The management of ADD is done by go- vernment of the Village Abbatireng of the District Gilireng of the Regency Wajo has followed the rules of the technical have been set out in the legislation. But in the process of reporting is not optimal yet. This is evident from the reporting and accountability that has been delayed. For the prosess reporting realization the use of ADD is not appropriate with the existing schedule, so it causing delays liquefaction of fund for the next stage. And so it is with the accountability the use of the ADD so the society can not evaluate the result the work of the Government of the village and accountability to the Local Government is not exact time. Secondly, the factor that influence Management Allocation Of Fund OF The Village (ADD) in the Village Abbatireng of the District Gilireng of the Regency Wajo include the factor supporter and the factor inhibiting. The factor supporter is The As for the factor be supporter that is participation society in terms of donate the lands to the Government of the village and facilities and infrastructure is adequate. But the factor inhibiting is human resources in terms officials government of village in the Village Abba- tireng average are hightschool cause the lack of knowlegde about management of ADD, directive of technical management of ADD every year is changing. It is cause the team of the activities of ADD have difficulties in the impelemtation their duty and communication in terms society that is less able to express opinions in public.